Dynamic modeling of ABA-dependent expression of the Arabidopsis RD29A gene - Ndathe, Ruth; Dale, Renee; Kato, Naohiro (Frontiers in Plant Science, 2022)
The abscisic acid (ABA) signaling pathway is the key defense mechanism against drought stress in plants. In the pathway, signal transduction among four core proteins, pyrabactin resistance (PYR), protein phosphatase 2C (PP2C), sucrose-non-fermenting-1-related protein kinase 2 (SnRK2), and ABRE binding factor (ABF) leads to altered gene expression kinetics that is driven by an ABA-responsive element (ABRE). A most recent and comprehensive study provided data suggesting that ABA alters the expression kinetics in over 6,500 genes through the ABF-ABRE associations in Arabidopsis. Of these genes, termed ABA gene regulatory network (GRN), over 50% contain a single ABRE within 4 kb of the gene body, despite previous findings suggesting that a single copy of ABRE is not sufficient to drive the gene expression. To understand the expression system of the ABA GRN by the single ABRE, a dynamic model of the gene expression for the desiccation 29A (RD29A) gene was constructed with ordinary differential equations. Parameter values of molecular-molecular interactions and enzymatic reactions in the model were implemented from the data obtained by previously conducted in vitro experiments. On the other hand, parameter values of gene expression and translation were determined by comparing the kinetics of gene expression in the model to the expression kinetics of RD29A in real plants. The optimized model recapitulated the trend of gene expression kinetics of RD29A in ABA dose–response that were previously investigated. Further analysis of the model suggested that a single ABRE controls the time scale and dynamic range of the ABA-dependent gene expression through the PP2C feedback regulation even though an additional cis-element is required to drive the expression. The model construed in this study underpins the importance of a single ABRE in the ABA GRN.